Minimizing and recycling of solid waste-primary elements in the solid waste management - Paunovic, Perica; Hadzi-Jordanov, Svetomir (Macedonian Journal of Ecology and Environment, 2001)
The main goal of this paper is to define basic activities of the Solid Waste Management (SWM) concept - Waste Reduction and Waste Recycling. The proposed scheme of SWM provides maximal recovery of Solid Waste usefull components as well as maximal decomposition of Solid Waste before its final disposal. The worldwide data of activities given in this paper give stimulus for their application in our country.